Impact of Carbohydrate-Electrolyte Beverage Ingestion on Heart Rate Response While Climbing Mountain Fuji at ~3000 m. (10th July 2017) - Horiuchi, Masahiro; Endo, Junko; Kondo, Koichi; Uno, Tadashi; Morikawa, Mayuko; Nose, Hiroshi
Abstract : We sought to investigate whether carbohydrate-electrolyte beverage ingestion reduced heart rate (HR) in twenty-three healthy young adults while climbing Mount Fuji at a given exercise intensity. Twenty-three healthy adults were randomly divided into two groups: the tap water (11 males [M] and 1 female [F]) and the carbohydrate-electrolyte group (10 M and 1 F). HR and activity energy expenditure (AEE) were recorded every min. The HRs for the first 30 minutes of climbing were not significantly different between the groups [121 ± 2 beats per min (bpm) in the tap water and 116 ± 3 bpm in the carbohydrate-electrolyte]; however, HR significantly increased with climbing in the tap water group (129 ± 2 bpm) but showed no significant increase in the carbohydrate-electrolyte group (121 ± 3 bpm). In addition, body weight changes throughout two days ascending and descending on Mount Fuji were inversely related to changes in resting HR. Further, individual variation of body weight changes was suppressed by carbohydrate-electrolyte drink. Collectively, carbohydrate-electrolyte beverage intake may attenuate an increase in HR at a given AEE while mountaineering at ~3000 m compared with tap water intake.